Towards realization of carbon nanotube spintronics devices fabricated by direct growth method - Mohamed, Mohd Ambri; Asyadi Azam, Mohd; Shikoh, Eiji; Fujiwara, Akihiko (2009)
Besides their high electronic conductivity, carbon nanotubes (CNTs) are expected to posses a long spin diffusion length due to their ideal -electron system with small spin-orbit interactions. The long spin diffusion length gives rise to spin-coherent transport: potential characteristics for spintronics devices. However, details of spin-dependent transport properties of CNTs have not yet been clarified. For the precise control of the charge and spin degrees of freedom, three basic processes, namely, injection, transport, and detection, have to be clarified. Towards the realization of CNT spintronics, we have investigated CNT devices fabricated by a direct growth method. Here, we report our work on the fabrication and characterization of CNT devices designed for the spin valve device.